2018
DOI: 10.1186/s12893-018-0449-5
|View full text |Cite
|
Sign up to set email alerts
|

Spigelian hernia in the right upper abdominal wall: a case report

Abstract: BackgroundSpigelian hernia (SH) is rare and constitutes less than 2% of all hernias. It is reported that more than 90% of SHs lie in the “Spigelian belt”, but SH in the upper abdominal wall is extremely uncommon. Here, we report a case of SH in the right upper quadrant of abdomen.Case presentationA 38-year-old female was admitted to hospital with complaints of abdominal pain and right upper quadrant mass for 10 days. Contrast-enhanced computed tomography (CECT) of abdomen revealed the dilated small intestine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…Ante la sospecha clínica de esta entidad, la ecografía es de utilidad, accesible y económica, aunque la TC es superior, ya que aporta datos como el tamaño del defecto, las características del saco y de su contenido, las relaciones anatómicas y no es operador dependiente, lo que la convierte en la prueba de elección [10][11][12] . A pesar de los grandes aportes de la ecografía y de la TC, existe un pequeño grupo de pacientes con HSC sintomáticos y estudios normales de imagen en el que el diagnóstico se confirma solo en la exploración quirúrgica 1 .…”
Section: Discussionunclassified
“…Ante la sospecha clínica de esta entidad, la ecografía es de utilidad, accesible y económica, aunque la TC es superior, ya que aporta datos como el tamaño del defecto, las características del saco y de su contenido, las relaciones anatómicas y no es operador dependiente, lo que la convierte en la prueba de elección [10][11][12] . A pesar de los grandes aportes de la ecografía y de la TC, existe un pequeño grupo de pacientes con HSC sintomáticos y estudios normales de imagen en el que el diagnóstico se confirma solo en la exploración quirúrgica 1 .…”
Section: Discussionunclassified
“…Spigelien's belt is an area about 6 cm wide above a transverse line that passes through the anterior superior iliac spines [5][6][7]. The higher incidence of hernias in this location is associated with the fact that in this location the posterior sheath of the rectus abdominis is absent and the fibers of the transversus abdominis and internal oblique muscle are in cross-parallel, making it a weakness point [5][6][7][8]15]. This does not happen above the umbilicus where there is the posterior sheath of the rectus abdominis and the fibers of the transversus abdominis and internal oblique muscles cross perpendicularly [6,7].…”
Section: Anatomymentioning
confidence: 99%
“…Concerning acquired defects, these can be associated with situations that increase intra-abdominal pressure, trauma or degeneration of the abdominal wall aponeurosis [6][7][8]15].…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Spigelian hernia is defined as a hernia occurring through the Spigelian aponeurosis. The herniation occurs through slit-like defects in the aponeurotic layer between the rectus abdominis muscle medially and the semilunar line laterally (so-called Spigelian fascia) [ 3 ]; it constitutes less than 2% of all hernias and is reported that more than 90% lie in the “Spigelian belt”[ 4 ]. Intraparietal inguinal hernias mimic Spigelian hernias clinically; although its treatment is very simple but pre-operative diagnosis is really a challenging issue [ 2 ].…”
Section: Introductionmentioning
confidence: 99%